Physical Activity and Weight Gain Prevention - Lee, I-Min (2010)
CONTEXT: The amount of physical activity needed to prevent long-term weight gain is unclear. In 2008, federal guidelines recommended ≥150min/week (7.5 MET-hr/week) of moderate-intensity activity for “substantial health benefits”. OBJECTIVE: To examine the association of different amounts of physical activity with long-term weight changes among women consuming a usual diet. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study, following 34,079 healthy, US women (mean age, 54.2 years) from 1992–2007. At baseline, 36-, 72-, 96-, 120-, 144- and 156-months’ follow-up, women reported their physical activity and body weight. Women were classified as expending <7.5, 7.5-<21, and ≥21 MET-hr/week of activity at each time. Repeated measures regression prospectively examined physical activity and weight change over intervals averaging 3 years. MAIN OUTCOME MEASURE: Change in weight. RESULTS: Women gained a mean of 2.6 kg throughout the study. In multivariate analysis, compared with women expending ≥21 MET-hr/week, those expending 7.5-<21 and <7.5 MET-hr/week gained 0.11 kg (SD=0.04; P=0.003) and 0.12 kg (SD=0.04; P=0.002), respectively, over a mean interval of 3 years. There was a significant interaction by body mass index (BMI), such that there was an inverse dose-response relation between activity levels and weight gain among women with BMI <25 kg/m(2) (P, trend <0.0001), but no relation among heavier women (P, trend=0.56 and 0.50, respectively, for BMI 25–29.9 and ≥30.0 kg/m(2)). A total of 4,540 women (13.3%) began the study with BMI <25 kg/m(2) and successfully maintained their weight, gaining <2.3 kg throughout; their mean activity level over the study was 21.5 MET-hr/week (~60 min/day moderate-intensity activity). CONCLUSION: Among women consuming a usual diet, physical activity was associated with less weight gain only among women with BMI <25 kg/m(2). Women successful in maintaining normal weight and gaining <2.3 kg over 13 years averaged ~60 min/day of moderate-intensity activity over the study duration.